Proceso de ASC - TRANSFERENCIA DE POLITICAS Y AGENDAS DE GENERO EN MEDELLIN (2021)
This project aims to investigate whether the recent inclusion of gender issues in the city's public agenda is the product, predominantly, of a policy transfer process in which certain exogenous factors (discourses and international action plans) and endogenous (internal, institutional, and non-institutional organizational dynamics) had a special impact on its consolidation. Using the literature review and the semi-structured interview as techniques, the different factors that have influenced the construction of the gender agenda of Medellín are analyzed. The main result highlights the fact that such construction is partly the product of policy transfer process, in which, added to the efforts of local women's movements and the political will of the municipal administration, has been consolidated in the form of public policies and has made the city a benchmark for the country and the region.